Analisis Rasio Profitabilitas Dan Rasio Likuiditas Untuk Menilai Kinerja Keuangan PT Indo Tambangraya Megah Tbk Periode 2014-2018 - E Y Suharyono 3, Justamal 1 Eka Yudhyani 2 (EKONOMIA, 2021)
This study was conducted to determine and analyze financial performance in terms of profitability ratios with Net Profit Margin (NPM), Return On Asset (ROA), and Return On Equity (ROE) indicators, and liquidity ratios with Current Ratio, Quick Ratio indicators, and PT Indo Tambangraya Megah Tbk's Cash Ratio during 2014-2018.The analytical tools used in this research are Net Profit Margin (NPM), Return On Asset (ROA) and Return On Equity (ROE), as well as Current Ratio, Quick Ratio, and Cash Ratio.Based on the profitability ratio of PT Indo Tambangraya Megah, Tbk during 2014-2018, there was an increase in Net Profit Margin (NPM) which indicates that the company's ability to generate profit on sales has also increased. Furthermore, there was an increase in Return On Asset (ROA) and Return On Equity (ROE), which shows the company's ability to generate a return on total assets and total equity owned has increased.Based on the liquidity ratio of PT Indo Tambangraya Megah, Tbk during 2014-2018, the Current Ratio has increased which shows that the company's ability to fulfill its short-term obligations when being billed has increased, in addition, there is an increase in Quick Ratio which shows that the company's ability to pay, fulfill liabilities or current debt (short-term debt) by using current assets without the need to take into account that inventory (supply value) has increased, as well as an increase in Cash Ratio which indicates that the company's ability to meet the availability of cash or cash equivalents to meet its short-term obligations in when billed has increased.Â